[Notes] (Journal of Political Economy, 1897)
THE publication of the results of the last quinquennial census of France, taken in the year I896, gives renewed evidence of the almost stationary state of French population. The total population for the eighty-seven departments included in the enumeration is 38,5I7,975, showing a gain of I75,027 on the year 189I, and of 299,072 for the decade I886-I896. But the real situation is only partly disclosed in these totals. For only twenty-four of the eighty-seven departments show any increase, the remaining sixty-three having experienced an actual decline of numbers, aggregating over 385,ooo, as compared with I89I. The explanation of this phenomenon is the continued drift of population from the rural districts toward the larger centers. Cities of over 30,000 inhabitants show an aggregate gain of 327,000, the three cities, Paris, Lyon, and Marseilles alone being credited with almost half this increase.